Work organisation and health at work in the European Union - Daubas-Letourneux, Véronique; Thébaud-Mony, Annie (Dublin, 2003)
"Based on findings from the Foundation’s Third survey of working conditions 2000, this report studies the connections between work organisation and working conditions. The authors first outline the typology of different forms of work organisation, from which they construct four distinct groups: ‘constrained’ work, ‘flexible’ work, ‘autonomous’ work and ‘automated’ work. Each of these organisational forms is shown to be subject to individual risks and injuries to health or personal dignity at the workplace. The report focuses on those groups which are more exposed than others and shows that the choice of work organisation can have an influence over a worker’s health and safety."